PROGRAM PENDETEKSIAN DISTRIBUSI PEWARISAN GENOTIP SUATU POPULASI UNTUK TIPE PEWARISAN AUTOSOMAL DENGAN METODE QR - Ernawati Ernawati; Joko Purwadi (Universitas Kristen Duta Wacana, 2011)
In Linear Algebra, finding eigenvalues of a big size matrix is not easy to do manually.Many problems in numerical applications need this eigenvalues. One of them is related withGenetics Science in detecting genotype inheritance distribution of a population. New ideasof computerized breeding program are being developed. This system only can be use by researcherswho at the minimum requirement knows about genotype inheritance in GeneticsBasis.This research tried to design a program to plan the exact breeding by considering thegenotypes of the parents that is breed, to get future genotypes of the offspring distributionthat is suitable with the user’s prospects. QR Method as one of the Numerical Method is implementedto find the eigenvalues needed in this case.The result of this research is a program that implemented QR Method in detectinggenotype inheritance distribution of a population for Autosomal inheritance type. Theprogram output are table and graph percentage comparation between genotype distributionof the early population with the predicted generation.